Centers of Excellence from the Danish National Research Foundation 1993-2005 - Alnor, Emil Dolmer; Schneider, Jesper Wiborg; Degn, Lise (CFA Scientific Reports, 2023)
The Danish National Research Foundation (DNRF) asked the Danish Center for Studies in Research and Research Policy (CFA) to conduct a retrospective analysis of the DNRF Centers of Excellence (CoEs) from the initial three rounds from 1993-2005. The rapport summarizes the analysis of 3 themes: 1) what elements of the CoE framework were effective in promoting excellence in research and why, 2) the impact of the CoE on the involved researchers, institutions, and society, and 3) potentials and challenges for the DNRF CoE as seen by involved researchers and institutions.